A SIMPLE WAY TO MODEL NONSYNCHRONOUS GENERATION OF OIL AND GAS FROM KEROGEN - Waples D.W.; Ramly M. (My University, 2001)
Many kinetic models for oil and gas generation use the same kinetics for generation of both oil and gas. In these models, gas is generated at precisely the same time as oil, despite agreement among geochemists that oil generation in nature largely precedes gas generation. Here we present a method for deriving separate kinetics for oil generation and gas generation from the available kinetics for total hydrocarbon generation. The method is based on published data in which oil kinetics are compiled separately from gas kinetics, but it is generalized to be applicable to any of the main kerogen types (I, IIa, IIb, or III), or to any mixtures of those types. Application of this new nonsynchronous model shows that the traditional synchronous models overpredict gas generation by about a factor of two within the oil window, and conversely severely underpredict late gas generation. The nonsynchronous model may predict gas generation several tens of million years later than does the synchronous model. The errors inherent in the synchronous models can be of significance in exploration decisions.
Keywords: GAS GENERATION; KINETICS; KINETIC MODELING; TIMING